Determination of Sugar Content in Fruit Juices Using High Performance Liquid Chromatography - Damayanti, Sophi; Permana, Benny; Weng, Choong Chie (Acta Pharmaceutica Indonesia, 2012)
Sugar is a sweet, water-soluble, crystallizable material which is obtained commercially from sugarcane or sugar beet. As an important source of dietary carbohydrate, a sweetener, preservative in foods and a cause factor for Diabetic disease, analysis of sugar content is needed. The objective of this study was to verify the suitability and determination of sugar content in fruit juices using HPLC. The fresh fruits except strawberries were peeled, cut and blended using homogenizer. After filtration, 12.5mL of each fresh juices and packed juices were diluted with acetonitrile and distilled water (50:50). The diluted fresh juices and packed juices were loaded onto C18 Sep-Pak cartridge. Fructose, glucose, and sucrose of each fresh juices and packed juices were analyzed in HPLC with Refractive Index detector, NH2 polar bonded phase column, 10Î¼m (250mm Ã4.6mm I.D.), temperature of 43.5Â°C, mobile phase of acetonitrile and 10mM sodium phosphate (monobasic) (78:22) and flow rate of 1.0mL/min. The method validation showed good linearity of equations for fructose, glucose and sucrose were y = 3833208.4806x â 94721.0361, y = 3782886.4708x â 101683.4708, y = 3770593.9638x â 82870.9083 with regression coefficients, r2 of 0.9995, 0.9997 and 0.9996 respectively. The calculated regression function coefficients (Vx0) for fructose, glucose and sucrose were 0.0152, 0.0112 and 0.0132% respectively. The percentage recovery of fructose, glucose, and sucrose was found to be in a range of each 86.681 â 89.888, 86.898 â 90.029, and 94.541 â 97.885%. Sugar contents in fruit juices can be determined using verified HPLC method with Refractive Index Detektor. Fructose, glucose and sucrose of fresh juices contained 0.469 â 1.431, 0.454 â 1.286, 0.544 â 1.861%, whereas that of packed juices contained 0.309 â 1.587, 0.261 â 0.762,0.063 â 0.898%, respectively.Keywords: Fructose, glucose, sucrose, fruit juice, HPLC.Gula merupakan zat yang berasa manis, larut dalam air, berbentuk kristal yang dapat diperoleh dari berbagai sumber antara lain bit gula dan tebu. Sebagai sumber karbohidrat, pemanis dan pengawet dari makanan, dan penyebab diabetes, maka kandungan gula perlu ditentukan. Tujuan dari penelitian ini adalah untuk verifikasi kesesuaian penentuan kadar gula dalam jus buah menggunakan Kromatografi Cair Kinerja Tinggi (KCKT). Buah segar kecuali stroberi dikupas kemudian dipotong dan dicampur dengan menggunakan homogenizer. Setelah disaring, 12.5mL jus segar dan 12.5mL jus kemasan diencerkan dengan asetonitril dan air suling (50:50). Jus segar dan jus kemasan kemudian dilewatkan melalui tabung C18 Sep-Pak. Fruktosa, glukosa dan sukrosa kemudian dianalisis menggunakan KCKT detektor Indeks bias, kolom NH2, 10Î¼m (250Î¼m Ã ID 4.6mm) dan suhu kolom 43.5ÂºC, fase gerak asetonitril dan larutan natrium fosfat 10mM (78:22) dan laju aliran adalah 1.0mL/min. Metode validasi menunjukkan linearitas persamaan yang baik untuk fruktosa, glukosa dan sukrosa yaitu y = 3833208,4806x â 94721,0361, y = 3782886,4708x â 101683,4708, y = 3770593,9638x â 82870,9083 dengan koefisien korelasi, r2 adalah 0,9995, 0,9997 and 0,9996 masing-masing. Koefisien fungsi regresi yang dihitung (Vx0) untuk fruktosa, glukosa dan sukrosa adalah 0,0152, 0,0112 dan 0,0132 %. Persentase perolehan kembali untuk fruktose, glukosa dan sukrosa berada dalam rentang masing-masing 86,681 â 89,888, 86,898 â 90,029, dan 94,541 â 97,885%. Kandungan fruktosa, glukosa dan sukrosa dapatditentukan dengan menggunakan kromatografi cair kinerja tinggi dengan detektor indek bias. Fruktosa, glukosa dan sukrosa jus segar mengandung 0,469 â 1,431, 0,454 â 1,286, 0,544 â 1,861% sementara pada jus kemasan mengandung masing-masing 0,309 â 1,587, 0,261 â 0,762, 0,063 â 0,898%.Kata kunci: Fruktosa, glukosa, sukrosa, jus buah, HPLC.